Does Students' Financial Behaviour Differ Based on Their Family Income? - Nano, Dorjana; Lukani, Teuta (European Journal of Economics and Business Studies, 2015)
This study investigates the differences on Financial Behaviour among Albanian university students based on their family income. The main objectives of this study are: i) firstly, to assess the level of financial behaviour of Albanian university students; ii) to examine whether the financial behaviour differs based on the level of students family income; and ii) finally, , to provide some conclusions and policy implications with regard to financial behaviour. An instrument comprised of specific and personal questions is administered to 637 students from five public and two private universities in Albania. Factor analysing and Cronbach Alpha test are utilized to assess the validity and reliability of the questionnaire. Data analysis is conducted based on the One Way Welch Anova technique. The outcomes discover that Albanian university students show almost a good financial behaviour which differs based on household income. Students with low or middle family income are revealed to show better financial behaviour in comparison with those who reported to have high level of family income. This study paves the way for future research in Albania and for taking incentives for helping students to shape healthy spending habits.
Keywords: financial behaviour, family income, Albanian university students.